The Relationship between Entry Grades of Students Admitted to Public Universities in Uganda under Direct Entry Schemes and Their Academic Performance: Implications for Admission Policies - Aciro, Rosalba; Oriangi, George; Onen, David; Malinga, Geoffrey M.; Ezati, Betty A.; Openjuru, George L. (East African Journal of Education Studies, 2023)
Although studies on relationships between entry qualification and academic performance show that students who excelled academically in entry qualification often perform better than those with low entry qualification in subsequent examinations, this argument has been questioned. This study explored the relationship between entry grades of undergraduate students and academic performance in public universities in Uganda in the first and final years of their studies. A retrospective cohort analysis of data for undergraduate students of Gulu and Makerere Universities using a sample of 2825 academic records from 2013-2016 was conducted. Descriptive statistics and Pearson correlation analysis were used for analysis. Results revealed a significant relationship between entry scores and students’ academic performance for those admitted on national merit, district quota, affirmative action schemes and private sponsorship schemes in four university programs. However, there was no significant correlation between entry scores and students’ academic performance in the Bachelor of Medicine and Bachelor of Surgery programs. Although male students joined with lower grades than females, their performance in the final year was better than their female counterparts. Therefore, this study confirms that the entry qualification score predicts academic outcomes in the early and exit stages of the university. These findings support the current Government entry criteria for public universities, provide important information for the admission committee decisions, and may have implications for admission policies. However, the lack of a significant correlation between entry qualification scores and students’ academic performance in Bachelor of Medicine and Bachelor of Surgery could indicate the need to revisit admissions criteria for this program. Future studies should go beyond the commonly used GPA to measure academic performance by including non-cognitive factors such as practical skills, clinical skills, and professionalism. Furthermore, the role of background and sociodemographic factors in influencing academic performance at public universities should be considered alongside the pre-entry qualification score